Advanced electric drives : analysis, control, and modeling using MATLAB/Simulink - Mohan, Ned (Wiley, 2014)
"Advanced Electric Drives utilizes a physics-based approach to explain the fundamental concepts of modern electric drive control and its operation under dynamic conditions. Gives readers a "physical" picture of electric machines and drives without resorting to mathematical transformations for easy visualization Confirms the physics-based analysis of electric drives mathematically Provides readers with an analysis of electric machines in a way that can be easily interfaced to common power electronic converters and controlled using any control scheme Makes the MATLAB/Simulink files used in examples available to anyone in an accompanying website Reinforces fundamentals with a variety of discussion questions, concept quizzes, and homework problems"--